KAJIAN PENGGUNAAN BANTALAN BETON BEKAS JALUR KERETA API SEBAGAI DINDING PENAHAN TANAH PENGGANTI GABION - Dicky Arisikam; Awan Hermawan Purwadinata; Nadia Laila Lathifah (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
On the railway track, a change in layout and space can be found oftenly in order to improve the function of the railway to be better and have a high degree of reliability. This research aimed to analyze the slope stability due to the load that occurs when used concrete sleepers instead of gabion, as well as to find out the safety factors of hiping construction using concrete sleepers. The calculation of railway slope stability considers three models of slope failure: failure due to bolsters, shear forces, and soil bearing capacity. The calculation results of slope stability and force that occurs in the reinforcement is verified using Plaxis 2D CE V20 software with the output in the form of safety factors. Based on the results of the research, the alternative reinforcement using used concrete pads as a substitute for gabions has a deformation value of 0.1058 m with a safety factor of 1.638. So, the alternative is safe against landslides during the construction period having an FK value > 1.5 exceeding the minimum safety factor value.